2010
DOI: 10.1097/acm.0b013e3181e0116f
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Using a Computerized Rounding and Sign-Out System to Reduce Resident Duty Hours

Abstract: Managing information for sign-out and rounding with the UW Cores system, to reduce time spent in recopying patient data and in rounding on patients, improved continuity and enhanced resident efficiency without weakening systemic defenses against error or jeopardizing patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 20 publications
0
64
0
Order By: Relevance
“…Only 1 of the 37 studies in our review used a randomized crossover design, 40 and 4 (11%) used nonrandomized control groups. 21,28,30,38 A recent editorial notes that ''randomization is not the 'gold standard' for medical education research,'' 55 but it emphasizes that use of ''.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 1 of the 37 studies in our review used a randomized crossover design, 40 and 4 (11%) used nonrandomized control groups. 21,28,30,38 A recent editorial notes that ''randomization is not the 'gold standard' for medical education research,'' 55 but it emphasizes that use of ''.…”
Section: Discussionmentioning
confidence: 99%
“…38 In 9 studies (24%), perception of patient safety and/or quality of care improved 22,27,31,36,39 ; better patient management 21,25 or fewer near misses 30 were reported; and there was a reduction in missed patients. 34 However, a randomized crossover study found no statistically significant differences in resident-reported unexpected events, medical errors, or adverse drug events when comparing the electronic handoff system to the standard systems used (ie, written lists, card based, or a team-developed spreadsheet), 40 and another study found no difference in reported unexpected events pre-to postimplementation of a new electronic handoff system. 41 Residents responding to a postcall survey reported an unexpected patient event that should have been anticipated during handoff in about onethird of patients in the old as well as the new system.…”
Section: Self-reported Measuresmentioning
confidence: 99%
“…Furthermore, EMR-integrated handoff systems have been shown to facilitate patient care handoffs, which might otherwise be "haphazard and error prone." 2,6,7 In June 2006, Bernstein et al 8 implemented an EMR-integrated electronic handoff tool on the medical/surgical wards at Lucile Packard Children's Hospital (LPCH) and documented its rapid adoption, improved physician workflow and improved physician satisfaction. The handoff tool was not adopted in the LPCH neonatal intensive care unit (NICU), where the layout of a well-established standalone Microsoft Access sign-out database better addressed the needs of the unit.…”
Section: Introductionmentioning
confidence: 99%
“…The sign-out tool is sufficiently flexible to be used by the team for prerounding and team rounding activities. 11 As another benefit, medical students gain exposure to the tool, which provides an opportunity to teach the importance of reducing errors during transitions of care.…”
Section: Introductionmentioning
confidence: 99%